European needlegrass (Stipa capillata L.) population found in the New Zoological Garden in Poznań, characterised by electrophoretically detected peroxidase and esterase variability - Wysocki, Adam; Krzakowa, Maria; Michalak, Marcin (Biodiversity: Research and Conservation, 2006)
Individual plants of Stipa capillata L. originating from the population in the New Zoological Garden in Poznań city (West Poland) were examined by electrophoresis of 2 enzyme systems: peroxidases and esterases. The results were compared to those obtained for populations originating from 2 natural stands near Chełmno (ca. 120 km away from Poznań). The populations proved to be monomorphic with respect to eroxidases and only slightly polymorphic with respect to esterases. The prevalence of G2G2 phenotype in the population from the zoo suggests that this population is of some distant origin.